The effect of HMGB1 on sub-toxic chlorpyrifos exposure-induced neuroinflammation in amygdala of neonatal rats. (2nd December 2015) - Tian, Jing; Dai, Hongmei; Deng, Yuanying; Zhang, Jie; Li, Ying; Zhou, Jun; Zhao, Mingyi; Zhao, Mengwen; Zhang, Chen; Zhang, Yuxi; Wang, Peipei; Bing, Guoying; et al.
Abstract: Chlorpyrifos (CPF), one of organophosphorus pesticides (OPs), is associated with developmental neurotoxicity. Inflammatory response is closely related with CPF-induced neurotoxicity. The present study aimed at exploring whether sub-toxic CPF exposure on neonatal rats results in neuroinflammation that mediated by HMGB1/TLR4/NF-κB signaling pathway in the amygdala. The neonatal rats were subcutaneously injected with 5 mg/kg CPF for 4 consecutive days (postnatal day 11–14) with or without HMGB1 inhibitor, glycyrrhizin. We assessed the levels of pro-inflammatory cytokines at 12, 24, and 72 h after CPF exposure. The role of HMGB1 on neuroinflammation in sub-toxic exposure during brain development was studied. CPF-treated neonatal rats exhibited a significant increase in the expression of pro-inflammatory cytokines, such as IL-6, TNF-α and HMGB1, and a significant increase in the activation of NF-κB in the amygdala after CPF exposure. Inhibited HMGB1 reduced the release of IL-6 and TNF-α, and inhibited activation of NF-κB. Our findings indicate that CPF exposure on developmental brain might induce the activation of neuroinflammation mediated by HMGB1/TLR4/NF-κB pathway in the amygdala.